Structured Education and Daily Reminders to Improve Medication Adherence in Tuberculosis Patients: A Case Study - Aulia Insani Latif; St Ramona Dini Fadjrianti J (PT.Mantaya Idea Batara, 2025)
Introduction: Background: Non-compliance with TB treatment is one of the main and most crucial challenges in global TB control efforts. This condition contributes to high rates of treatment failure. Approximately 40% of patients in developing countries are known to have low compliance with pulmonary TB treatment. Methods: This was a descriptive case study using a pre- and post-test approach. The instrument used in this case study was the 8-Item Morisky Medication Adherence Scale questionnaire to measure the level of medication adherence among tuberculosis patients, namely Ms. S. This study was conducted in the treatment room of the Infection Center RSUP Wahidin Sudirohusodo Makassar held from June 27, 2025 to July 11, 2025. Before conducting the intervention, the researchers obtained informed consent from the patients and their families, and the study obtained permission from the hospital. Result: The provision of structured educational interventions and daily reminders in the form of reminder books can be considered effective in improving medication adherence among TB patients, as evidenced by the post-intervention questionnaire score of 6 (moderate adherence level), which increased from the pre-intervention questionnaire score of 1 (low adherence level). Conclusion: From this case study, it was found that the implementation of structural educational interventions and daily reminders was effective in improving medication adherence among TB patients.